2016
DOI: 10.1016/j.bbagrm.2015.06.015
|View full text |Cite
|
Sign up to set email alerts
|

lncRNAs and microRNAs with a role in cancer development

Abstract: Most diseases, including human cancer, are frequently associated with an altered transcription pattern. The alteration of the transcriptome is not restricted to the production of aberrant levels of protein-coding RNAs, but also refers to the dysregulation of the expression of the multiple noncoding members that comprise the human genome. Unexpectedly, recent RNA-seq data of the human transcriptome have revealed that less than 2% of the genome encodes protein-coding transcripts, even though the vast majority of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
349
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 466 publications
(360 citation statements)
references
References 97 publications
(109 reference statements)
5
349
0
3
Order By: Relevance
“…The other main group of ncRNAs is the long ncRNAs (lncRNAs; arbitrarily >200 nt), which are defined as lacking protein-coding potential but otherwise often display mRNA-like properties, including multiexonic gene structures and poly(A) tails (2,3). LncRNAs are associated with a variety of regulatory functions, including chromatin-related roles, splicing control, and transcriptional regulation (7)(8)(9). Despite recent reports describing aberrant expression of lncRNAs in human tumors (8)(9)(10)(11), few of these molecules have been carefully characterized with respect to their functional roles in the promotion or inhibition of carcinogenesis (12,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The other main group of ncRNAs is the long ncRNAs (lncRNAs; arbitrarily >200 nt), which are defined as lacking protein-coding potential but otherwise often display mRNA-like properties, including multiexonic gene structures and poly(A) tails (2,3). LncRNAs are associated with a variety of regulatory functions, including chromatin-related roles, splicing control, and transcriptional regulation (7)(8)(9). Despite recent reports describing aberrant expression of lncRNAs in human tumors (8)(9)(10)(11), few of these molecules have been carefully characterized with respect to their functional roles in the promotion or inhibition of carcinogenesis (12,13).…”
mentioning
confidence: 99%
“…LncRNAs are associated with a variety of regulatory functions, including chromatin-related roles, splicing control, and transcriptional regulation (7)(8)(9). Despite recent reports describing aberrant expression of lncRNAs in human tumors (8)(9)(10)(11), few of these molecules have been carefully characterized with respect to their functional roles in the promotion or inhibition of carcinogenesis (12,13). However, significant exceptions exist, and mechanisms of action and downstream cellular effects have been demonstrated for lncRNAs acting as oncogenes, such as HOTAIR (14) and MALAT1 (15), or as tumor suppressors, such as LincRNA-p21 (16) and Uc.283+A (17).…”
mentioning
confidence: 99%
“…5 Growing evidence suggests that lncRNAs are key players in cancer. 6,7 Up to now, lncRNAs have been demonstrated to play vital roles in tumour initiation, progression and metastasis through modulating oncogenic and tumour-suppressing pathways. 8,9 In addition, recent studies have indicated that a number of lncRNAs are dysregulated in gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…They play diverse structural and regulatory roles in cells such as chromatin modification, transcription, and REVIEW posttranscriptional processing. Except for diverse biological processes, different studies have already shown that aberrant lncRNA expression may result in the progression of human diseases, including cancers [3] .…”
Section: Introductionmentioning
confidence: 99%
“…The ncRNAs can be categorized into several groups, long non-coding RNAs (lncRNAs), such as microRNAs (miRNAs), small interfering RNAS (siRNAs), small nuclear (snRNAs), small nucleolar RNAs (snoRNAs), and piwi-interacting RNAs (piRNAs), etc. NcRNA may play a crucial role in cellular proliferation, physiology and pathologies although initially considered to be transcriptional noise or artifacts [2,3] . NcRNAs can also be grouped into two major groups according to their size.…”
Section: Introductionmentioning
confidence: 99%